2018
DOI: 10.1021/acsanm.8b00554
|View full text |Cite
|
Sign up to set email alerts
|

Microfluidics-Assisted Synthesis of Cross-Linked Colloidosomes with Multisensitive Behaviors: A Potential Platform for Photo Memory Device and Blue-Light-Triggered Release Vehicle

Abstract: Uniformly sized and cross-linked colloidosomes were prepared via microfluidic emulsification combined with a post-cross-linking reaction between NH 2 /ruthenium dual-functionalized microgels and poly(N-isopropylacrylamide)-r-(N-acryloxysuccinimide)-based polymers. When mixed with catalyst-free Belousov− Zhabotinsky reaction substrates, the colloidosomes first experienced decrease in size and then exhibited mechanical oscillations. In addition, the colloidosome behavior can be regulated using different types of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 58 publications
(87 reference statements)
0
19
0
Order By: Relevance
“…Finally, the residual toluene was rinsed with a large amount of deionized water. This complex structure provides the possibility of encapsulating different components in different cavities of a capsule …”
Section: Colloidal Crystals Synthesized By Microfluidicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the residual toluene was rinsed with a large amount of deionized water. This complex structure provides the possibility of encapsulating different components in different cavities of a capsule …”
Section: Colloidal Crystals Synthesized By Microfluidicsmentioning
confidence: 99%
“…This complex structure provides the possibility of encapsulating different components in different cavities of a capsule. [161][162][163][164][165][166][167][168]…”
Section: Microfluidic Synthesis Of Colloidosomesmentioning
confidence: 99%
“…The widespread application of optical fibers for optical signal transmission and the ongoing development of high‐speed optical computing have created a growing need for developing light‐writing memories . Compared to conventional electrically programmed memories, photomemory devices adopt the photon‐programming and store the light information instead, which is an essential block for optical data processing and photonic computation circuits .…”
Section: Introductionmentioning
confidence: 99%
“…Microcapsules in many forms play active roles in our daily lives. , Microcapsules have been fabricated using a variety of methods, including microfluidics, layer-by-layer self-assembly, and template and core removal. As one of the most powerful techniques, microfluidics has been intensely investigated for the fabrication of microcapsules with various structures. According to their building blocks, these capsule structures include vesicles, colloidosomes, and other conventional objects with hollow structures. A large number of attempts have been made to prepare microcapsules that can store a payload inside their lumen and release it in a controlled manner. , Weitz et al and Kim et al reported the microfluidic fabrication of capsules with various structures that undergo either the stimuli-triggered release of a single component or the programmed release of multiple hydrophilic payloads, and these are typical examples of such materials. However, rapid leakage of the cargos, particularly small molecule-based cargos, during the sample fabrication and incubation process remains a challenge. Chu et al developed so-called Trojan Horse-like microcapsules, which consisted of two distinct pH-responsive hydrogel layers with two separate oil layers between them.…”
Section: Introductionmentioning
confidence: 99%